Wireline techniques for monitoring reservoir fluid movement and recommendations for Malaysian oil and gas fields - Ramachandran, Supramaniam; Abd. Rahman, Mohd. Norani (Faculty of Chemical & Natural Resources Engineering, 1987)
This paper presents the wireline techniques used in reservoir monitoring and shows how the location and monitoring of variations in water, oil and gas saturations in producing wells, plays a significant role in determining the depletion profiles. Field data from a Malaysian Oil Field is analysed to illustrate how this wireline techniques help in determining the water, oil and gas saturations and provide information necessary to overcome well and reservoir problems. Necessity of a systematic approach in reservoir monitoring is emphasized in order to study the movement of GOC and WOC contacts and to know the distribution of remaining oil during primary or subsequent depletions.